AB0623 Prognostic value of renal resistive index (RRI) in systemic sclerosis: preliminary data from a single centre. (15th June 2017) - Bruni, C; Maestripieri, V; Tesei, G; Chiostri, M; Sambalino, C; Guiducci, S; Bellando-Randone, S; Boddi, M; Matucci-Cerinic, M
Abstract : Background: Renal Resistive Index (RRI- measured with Renal arteries Doppler ultrasound) is a useful technique to evaluate vascular and tubular-interstitial damage in both general and systemic sclerosis (SSc) population, where increased RRI values correlates with longer disease duration [1], lower glomerular filtration rate and more advanced nailfold-videocapillaroscopy pattern [2]. Moreover, higher RRI values were seen in SSc patients with new occurrence of digital ulcers [3]. Objectives: to test the prognostic value of RRI [absolute, ≥0.70 and SSc age-adjusted pathologic value (Table1 )] and RRI delta change in predicting general and organ-specific worsening in scleroderma patients. Methods: SSc patients classified according to ACR/EULAR 2013 criteria were enrolled. Demographics data and renal ultrasound data were collected. Data on clinical worsening had been collected as herewith specified: a) Skin worsening as an increase of mRSS≥5 units, b) Peripheral vascular worsening as the appearance of new digital ulcers or the worsening of nailfold videocapillaroscopy scleroderma pattern, c) Lung worsening as decline of FVC≥15% or FVC<80% with new detection of ILD on chest HRCT or worsening of HRCT-ILD extent, d) Cardiac worsening as new onset of left ventricular failure requiring treatments or new onset of PAH confirmed on RHC or detection of severe ventricular arrhythmias on 24h EKG, e) Renal worsening as a new scleroderma renal crisis or reduction of creatinine clearance ≤30 ml/min. General worsening was recorded in case of death due to SSc or for any of the above organ-specific worsening. Data were analysed as appropriate with SPSS vers. 20.0. Results: 190 SSc patients (age 56.3±15.0 yrs, 170 women, disease duration 6±8yrs, 65 with a follow up RRI measurement after 2.8±0.9 years) were enrolled. After a mean clinical follow-up of 3.6±2.6 years, 89 (46.8%) pts showed general worsening. Skin, peripheral vascular, cardiac, lung and renal worsening were detected in 14 (7.4%), 40 (21%), 32 (16.8%), 38 (20%) and 11 (5.8%) patients respectively. We registered 10 (5.2%) deaths and 43 (22.6%) patients with multiple organ worsening. Both absolute value of RRI and ≥0.70 RRI cut-off showed no significant association with organ or global clinical worsening, At the opposite, RRI cut-offs adjusted for age were associated with cardiac worsening (p=0.065 =- Figure 1 ). When in 65 patients the pattern of delta RRI and clinical worsening were analysed (Table 1 ), wider RRI changes were associated with general worsening (p=0.029) and cardiac worsening (p=0.006). The significance of these associations increased when sub-analyse was repeated focused on patients with normal SSc age-adjusted RRI values at baseline evaluation (p=0.017 and p<0.001 respectively, Figure 1 ). Conclusions: increase in RRI could be used as a sentinel sign for general and cardiac worsening in SSc patients, especially when age-related RRI variations are taken into account. References: Rivolta R, Arthritis Rheum. 1996. Rosato E, Semin Arthritis Rheum. 2012. Rosato E, Arthritis Care Res (Hoboken). 2014. Disclosure of Interest: None declared